Propuesta urbana de recuperación y consolidación del espacio público - barrio los Machines, Neiva Huila. (2023)
The informal settlements in Neiva, Huila do not have optimal habitability and comfort conditions, an example is the Los Machines settlement, located in areas of high risk of mass removals and torrential floods, making the houses and their inhabitants a vulnerable fragment due to because they do not have construction or architectural systems, likewise, a road system in poor condition disjointed with the city. In this research, a sustainable housing model was developed to improve habitability, architectural and construction conditions. Where, an analysis was carried out at different scales that allowed establishing the problems of the study area and identifying the relocation area and its potentialities, in which an urban design was projected that maintained the articulation with the environment and different typologies were generated. of housing from a matrix of sustainability strategies in order to obtain an adequate model that would respond to the needs of the population, built with ecological materials that are friendly to the environment and that could have a progressive development in the future.